Curcumin alleviated the toxic reaction of Rhizoma Paridis saponins in a 45‐day subchronic toxicological assessment of rats. Issue 12 (22nd September 2015) - Man, Shuli; Li, Jing; Liu, Jing; Chai, Hongyan; Liu, Zhen; Wang, Jiaming; Gao, Wenyuan
ABSTRACT: Rhizoma Paridis saponins (RPS), as steroid saponins, are the main components in Paris polyphylla . Curcumin (diferuloylmethane) is the most important component in the spice turmeric. In our previous research, RPS exhibited side effects such as nausea, vomiting, diarrhea, and so forth. Combination with curcumin not only alleviated the toxicity and gastric stimulus induced by RPS, but also improved the quality life of mice bearing tumor cells and enhanced their anticancer effect. This study evaluated subchronic toxicity of 45 th dietary of RPS and curcumin on histopathology, biochemistry, and antioxidant index. As a result, RPS‐treatment caused a slight liver injury (the elevation of serum AST, alkaline phosphatase (AKP), alanine transaminase (ALT), and gamma glutamyl transpeptidase (γ‐GT), histopathological changes in liver section), oxidative stress (the enhancement of reactive oxygen species (ROS), malondialdehyde (MDA), and 8‐hydroxy‐2‐deoxyguanosine (8‐OHdG), separation of thioredoxin (Trx) and thioredoxin‐interacting protein (TXNIP), but enhancement of heme oxygenase‐1 (HO‐1), glutathione S‐transferase (GST), and nuclear factor‐regulated factor 2 (Nrf2)), and inflammation (up‐regulation of cyclooxygenase‐2 (COX‐2), interleukin‐1β (IL‐1β), and nuclear factor kappaB (NF‐κB)). However, these changes were alleviated through co‐treatment with curcumin. In conclusion, our work provided useful data for further research and new drug exploration of RPS and curcumin. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1935–1943, 2016.